Adjustment Of The Need For Land Water Signs On The Musi River Flow - Bambang Setiawan; Miran Miran; Firda Maria Tutuz Fatimatuz (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
16 Ilir River Port is a port located in the city of Palembang. There are obstacles along the Musi river shipping lane so that instructions/information must be given for safety on the way, one of which is inland water signs but the condition is not maintained and there are signs that are missing, damaged, and have been covered by trees, it is necessary to install signs according to their needs. The aims of this study are as follows: To determine the need for river signs in the Musi River area. To determine the placement of river signs in the area of ​​Palembang City (Pulo Kerto) to Banyuasin Regency (Muara Sungsang). To stipulate technical specifications for signs in terms of the shape and size of inland water signs. The research methodology used is observation, library/documentation (literature) and institutional. The analysis used is the analysis of the need for river signs, analysis of the placement of river signs, analysis of the technical specifications of signs in terms of the shape and size of the signs. The results of this study are the addition of Mainland Water Signs on the Musi River shipping channel as many as 98 signs to support safety, security, necessity, and discovery of past currents. Placement of river signs in the area of ​​Palembang City (Pulo Kerto) to Banyuasin Regency (Muara Sungsang). There are points of vulnerable locations such as bends, crossroads that are not yet complete with inland water signs and also obstacles.